ISLAMIC ARCHITECTURE APPROACH ON ISLAMIC ARTS GALLERY WONOSOBO - Umi Yuda Muzayanah (Fakultas Ekonomi (FE) dan Fakultas Teknik dan Ilmu Komputer (FASTIKOM) Universitas Sains Al Qur'an, 2021)
sound, and others. With this Islamic art, beauty is able to deliver the servants of Muslims to their God. Wonosobo is one of the districts with a rich variety of Islamic arts, in addition to the fact that the majority of its citizens are Muslim, Wonosobo Regency is also a “santri” city that has many Islamic Education Institutions. From this Islamic Education Institute, several works of Islamic art were produced. To appreciate the works of Islamic art from the Wonosobo community and artists from students, Wonosobo Regency needs to have a building that is used as a forum for art appreciation. With the concept of Islamic architecture, this building is able to become the place intended to make this happen. Apart from being in accordance with building friends, namely Islamic buildings, the Islamic architectural approach will add to the beauty of this building. By using a descriptive analysis discussion to conduct a comparative study. Where later the form of the building will be adjusted to the approach as determined, namely Islamic Architecture.